Making cars more fuel efficient technology for real improvements on the road (OECD, 2005)
"The European Conference of Ministers of Transport has released a report that analyzes the gap between fuel efficiency certification test ratings and the actual on-road fuel efficiency of automobiles. The report also examines technologies available that could reduce that gap and improve fuel economy. In addition, the report identifies a number of low-cost technologies that could improve average on-road fuel economy by 10% or more and explores policies that could be used to encourage uptake of these technologies by vehicle manufacturers and consumers."--publisher summary.